Removal of Hexavalent Chromium from Aqueous Solution using Vigna Radiata Husk (Green Gram) - Saravanakumar, K.; Kumar, A. (Asian Journal of Chemistry, 2011)
In this study, Vigna radiata Husk (VRH) activated carbon was prepared and used to remove Cr(VI) from aqueous solution. The influences of initial Cr(VI) ion concentration (250-1000 mg/L), pH (1-11), adsorbent dose (0.25-2.5 g), contact time (15-150 min) and particle size (0.15-0.85 mm) had been reported. A comparison of isotherm models applied to the adsorption of Cr(VI) ions on the adsorbent was evaluated for Langmuir, Freundlich and Redlich Peterson isotherms. Adsorption of Cr(VI) was highly pH dependent and the results indicate that the optimum pH for the removal was found to be 2. The obtained results showed that the adsorption of Cr(VI) by Vigna radiata Husk follows Redlich-Peterson isotherm equation with a correlation coefficient equal to 0.99. In addition, the kinetics of the adsorption process follows the pseudo secondorder kinetic model. The results indicate that Vigna radiata Husk can be employed as a low cost alternative to commercial adsorbents in the removal of Cr(VI) from water and wastewater.